Queilite actínica em trabalhadores da construção civil do município de Feira de Santana, Bahia - Queiroz, Laís Ramos (2016)
Actinic cheilitis is a potentially malignant disorder of inflammatory nature, which affects the lip, mostly the lower lip. The lesion is caused by prolonged and excessive exposure to sunlight, occurring mainly in white males that perform activities exposed to the sun. The aim of this study was estimate the prevalence of actinic cheilitis and identify the factors associated with this lesion for construction workers who worked on construction sites in the city of Feira de Santana, Bahia, in the year of 2015. This work is an epidemiological cross-sectional survey. The study sample consisted of 319 construction workers of both genders. For data collection, interviews were conducted to obtain demographic information, professional occupation, lifestyle, and the use of photoprotection measures. In addition, all employees underwent oral examination and procedures for the diagnosis of actinic cheilitis. The workers were mostly male (99.4%), black (48,3%), and mean age of 37 years. Most were from urban areas (51.7%), married (36,7%), and schooling level was incomplete primary education (50,2%). The average monthly income was R$1,139.28.The prevalence of actinic cheilitis among study participants was 13.5% (CI 95%: 10,2 – 17,7). An association was found between the presence of the lesion and 1) white skin color (PR=5,44; CI 95%: 3,37-8,80), 2) age greater than or equal to 37 years (PR=1,98; CI 95%:1,06-3,69), 3) working time in construction greater than or equal to 10 years (PR = 2,26; CI 95%: 1,29-3,27). A high prevalence of actinic cheilitis was observed in construction workers, indicating the need for educational and preventive measures on occupational risk of solar radiation and other risk factors for oral cancer in this population.